Perceptions of In-Service Teachers Towards CLIL and CLIL Teachers’ Target Language and Intercultural Competences: The Context of English-Medium Instruction Schools in Thailand - Taylor, Pimsiri (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This study is aimed at investigating the perceptions of in-service English-medium instruction (EMI) teachers towards CLIL and CLIL teachers’ target language and intercultural competences. The participants were 59 Thai/local and international native English-speaking teachers (NESTs) and non-native English-speaking teachers (NNESTs) at EMI schools in Thailand. The participants attended the one-day CLIL teacher training workshop used as the research context of the study. Questionnaire and audio recordings of the workshop were used as instruments in collecting both quantitative and qualitative data. Results indicated that Thai teachers generally perceived their CLIL knowledge and competences as the lowest in all areas. International NNESTs, by contrast, ranked themselves the highest in most areas, except for overall target language competence, where their perceived competence was slightly lower than international NESTs. These results can raise question of whether NESTs are more competent in EMI classrooms. Through thematic analysis, it was found that opportunities to learn and share about CLIL, to use English in intercultural settings, and to learn about intercultural awareness can contribute to EMI/CLIL teacher competences. Recommendations are provided regarding CLIL teachers’ professional development for local and international teachers in the Thai EMI school contexts and alike.